2023
DOI: 10.3352/jeehp.2023.20.01
|View full text |Cite
|
Sign up to set email alerts
|

Are ChatGPT's knowledge and interpretation ability comparable to those of medical students in Korea for taking a parasitology examination?: a descriptive study

Abstract: This study aimed to compare the knowledge and interpretation ability of ChatGPT, a language model of artificial general intelligence, with those of medical students in Korea by administering a parasitology examination to both ChatGPT and medical students. The examination consisted of 79 items and was administered to ChatGPT on January 1, 2023. The examination results were analyzed in terms of ChatGPT's overall performance score, its correct answer rate by the items’ knowledge level, and the acceptability of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
1
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 4 publications
6
94
1
5
Order By: Relevance
“…For instance, Gilson et al (2022) found that ChatGPT performed comparably to medical students on medical licensing exams, while de Winter (2022) reported that ChatGPT's performance on English comprehension was similar to that of university students. Conversely, Huh (2023) found that ChatGPT's overall performance on a parasitology exam was lower than that of medical students in Korea. Similarly, Geerling et al (2023) found that ChatGPT achieved high performance in a university exam measuring economics knowledge.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For instance, Gilson et al (2022) found that ChatGPT performed comparably to medical students on medical licensing exams, while de Winter (2022) reported that ChatGPT's performance on English comprehension was similar to that of university students. Conversely, Huh (2023) found that ChatGPT's overall performance on a parasitology exam was lower than that of medical students in Korea. Similarly, Geerling et al (2023) found that ChatGPT achieved high performance in a university exam measuring economics knowledge.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, AI chatbots such as ChatGPT can offer prompt feedback and corrections to questions, thereby assisting students in comprehending intricate concepts that are difficult to learn (Cotton, Cotton & Shipway, 2023). By using AI chatbots, students can benefit from personalized, interactive learning experiences, and better manage their time by planning their assignments and homework (Cotton, Cotton & Shipway, 2023;Huh, 2023;O'Connor & ChatGPT, 2023).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Scientists must be able to assess the correctness of AI-generated medical information and develop credibly, validated information for patients and the general public [ 4 , 7 ]. As a result, it is vital to establish the precision with which ChatGPT, a recently built AI chatbot, can answer queries.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is vital to establish the precision with which ChatGPT, a recently built AI chatbot, can answer queries. This comparison of ChatGPT's capabilities may shed light on whether and how scientists and users could benefit from ChatGPT for learning and research purposes [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation